PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE ARTIKULASI DAN BERTUKAR PASANGAN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU DI KELAS VII SMP NEGERI 6 KOTA JAMBI - Zulhen, Annisa; Andriani, Lili (SJEE (Scientific Journals of Economic Education), 2021)
AbstractThis study aims to determine (1) Whether there is a difference in the average learning outcomes of Integrated IPS in students whose learning uses the Articulation learning model, (2) Whether there is a difference in the average learning outcomes of Integrated IPS in students whose learning uses the Pair Exchange learning model, and (3) Whether there is an influence on the learning outcomes of Integrated IPS in students whose learning uses the Articulation learning model and the Pair Exchange learning model. This type of research is a quasi -experiment. The total population in this study was 235 people. The sampling technique in this study is purposive sampling, so that 40 students of class VII C were selected as the Control class and 39 students of class VII F as the Experimental class. The technique of data collection in this study is to disseminate questions to research respondents and documentation. The data analysis technique in this research is t test using SPSS for Windows Version 16. The results showed that (1) The learning outcomes of students in IPS subjects taught using Articulation type cooperative learning model obtained a mean of 63.59 (2) The learning outcomes of students in Integrated IPS subjects taught using Cooperative learning model of the Exchange type pair obtained a mean score (mean) is 54.12 and (3) The learning outcomes of students in the subjects of Integrated IPS taught using the cooperative learning model of the Articulation type are higher than the student learning outcomes in the subjects Integrated IPS taught using the Cooperative Learning model of Pair Exchange with a value of 0.000> 0.05. Based on the research results obtained, it can be concluded that there is an influence on the use of cooperative learning model type Articulation on student learning outcomes in Integrated IPS subjects in class VII SMP Negeri 6 Kota Jambi. Keywords: Articulation Type Cooperative Learning Model, Pair Exchange Type Cooperative Learning Model, Learning Outcomes.